2019
DOI: 10.3390/ijms20112849
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Cerato-Platanin-Like Protein FocCP1 from Fusarium oxysporum Triggers an Immune Response in Plants

Abstract: Panama disease, or Fusarium wilt, the most serious disease in banana cultivation, is caused by Fusarium oxysporum f. sp. cubense (FOC) and has led to great economic losses worldwide. One effective way to combat this disease is by enhancing host plant resistance. The cerato-platanin protein (CPP) family is a group of small secreted cysteine-rich proteins in filamentous fungi. CPPs as elicitors can trigger the immune system resulting in defense responses in plants. In this study, we characterized a novel cerato-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 72 publications
(97 reference statements)
0
32
0
Order By: Relevance
“…Enolase is one of the key enzymes in glycolysis, and has also been reported in an animal pathogen that requires the combination of enolase and β-1,3-glucanase for the complete virulence [ 39 ]. On the other hand, some of the previously reported effectors of Foc TR4 , including FocCP1 [ 17 , 20 ], Six1a [ 18 ], and Six8 [ 19 ] have not been identified ( Supplementary Table S1 ). In two recent articles describing the function of FocCP1 in banana infection, one reported that this protein was required for full virulence of Foc TR4 [ 20 ], while the other considered that it triggered immune reaction [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enolase is one of the key enzymes in glycolysis, and has also been reported in an animal pathogen that requires the combination of enolase and β-1,3-glucanase for the complete virulence [ 39 ]. On the other hand, some of the previously reported effectors of Foc TR4 , including FocCP1 [ 17 , 20 ], Six1a [ 18 ], and Six8 [ 19 ] have not been identified ( Supplementary Table S1 ). In two recent articles describing the function of FocCP1 in banana infection, one reported that this protein was required for full virulence of Foc TR4 [ 20 ], while the other considered that it triggered immune reaction [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some of the previously reported effectors of Foc TR4 , including FocCP1 [ 17 , 20 ], Six1a [ 18 ], and Six8 [ 19 ] have not been identified ( Supplementary Table S1 ). In two recent articles describing the function of FocCP1 in banana infection, one reported that this protein was required for full virulence of Foc TR4 [ 20 ], while the other considered that it triggered immune reaction [ 17 ]. However, in this study, FocCP1 was not identified in Foc TR4 (EMT67648.1), and only a small number of the matched peptides were identified in Foc R1 (ENH63703.1) ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CP proteins also enhance the virulence of necrotrophic fungi, as many of them are expressed during –pathogen interactions and induce death of the affected tissue [24,41]. It was recently shown that FocCP1, which is identified in the secretome of Foc , triggered an immune response and caused systemic acquired resistance (SAR) in tobacco [42]. In our study, treating banana leaves with purified FocCP1 protein, acting as a virulence effector, induced cell death and upregulated expression of defence-related genes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Till now, in addition to CP, 11 more CPP family CIDPs have been identified from different fungal pathogens ( Table 2 ), such as BcSpl1 in B. cinerea ( Frías et al, 2011 , 2013 ), EPL1 in Colletotrichum falcatum ( Ashwin et al, 2017 ), CgCP1 in Colletotrichum gloeosporioides ( Wang W. et al, 2018 ), Pop1 in Ceratocystis populicola ( Comparini et al, 2009 ), FgCPP2 in F. graminearum ( Quarantin et al, 2016 , 2019 ), FocCP1 in Fusarium oxysporum ( Li et al, 2019a ; Liu et al, 2019 ), HaCPL2 in Heterobasidion annosum sensu stricto ( Chen et al, 2015 ), MoSM1/MSP1 ( Jeong et al, 2007 ; Yang et al, 2009 ; Wang et al, 2016 ; Hong et al, 2017 ) in M. oryzae , MpCP1 in Moniliophthora perniciosa ( Zaparoli et al, 2009 ), SsCP1 in Sclerotinia sclerotiorum ( Yang et al, 2018b ), and VdCP1 in Verticillium dahliae ( Zhang et al, 2017a ). Similar to CP, these 11 CPP family CIDPs induced strong necrosis and elicited defense responses in plants.…”
Section: Major Protein Families Of Oomycete and Fungus Apoplastic CDImentioning
confidence: 99%